Hubungan Motivasi dan Kepuasan Kerja terhadap Kinerja Penyuluh Kehutanan - Selfi, Selfi; Golar, Golar; Muis, Hasriani (Mitra Sains, 2022)
This research aims to describe and analyze the profile, level of motivation, job satisfaction and performance of forestry instructors at the Lore Lindu National Park Office (LLNPO). The research results show that the profile of forestry instructors is "young" (under 30 years), and has relatively recent work experience. Currently, their work experience is generally less than 10 years. However, formally the level of education is "high" (bachelor's degree). Motivation and level of job satisfaction of forestry instructors are classified as "good". This means that forestry instructors are satisfied with their work and performance as forestry instructors. The results of the analysis also show that the performance level of forestry instructors is in the "medium" category. However, forestry instructors do not fully understand the planned activities so they cannot be implemented optimally. This can affect the fulfillment of the credit score that will be submitted as a condition for promotion. Based on the results of the correlation analysis, it shows that there is no significant relationship between the profile and job satisfaction of forestry instructors and their performance, but there is a real relationship between the work motivation of forestry instructors and their performance.